Coloured Petri Nets - a Pragmatic Formal Method for Designing and Analysing Distributed Systems - Mortensen, Kjeld Høyer (DAIMI Report Series, 1997)
The thesis consists of six individual papers, where the present paper contains the mandatory overview, while the remaining five papers are found separately from the overview. The five papers can roughly be divided into three areas of research, namely case studies, education, and extensions to the CPN method. The primary purpose of the PhD thesis is to study the pragmatics, practical aspects, and intuition of CP-nets viewed as a formal method for describing and reasoning about concurrent systems. The perspective of pragmatics is our leitmotif, but at the same time in the context of CP-nets it is a kind of hypothesis of this thesis. This overview paper summarises the research conducted as an investigation of the hypothesis in the three areas of case studies, education, and extensions. The provoking claim of pragmatics should not be underestimated. In the present overview of the thesis, the CPN method is compared with a representative selection of formal methods. The graphics and simplicity of semantics, yet generality and expressiveness of the language constructs, essentially makes CP-nets a viable and attractive alternative to other formal methods. Similar graphical formal methods, such as SDL and Statecharts, typically have significantly more complicated semantics, or are domain-specific languages. research conducted in this thesis, opens a new complex of problems. Firstly, to get wider acceptance of CP-nets in industry, it is important to identify fruitful areas for the effective introduction of the CPN method. Secondly, it would be useful to identify a few extensions to the CPN method inspired by specific domains for easier adaption in industry. Thirdly, which analysis methods do future systems make use of?